2022
DOI: 10.47750/pnr.2022.13.s09.166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Relationship Between Bmi and Blood Pressure Among Underprivilaged Tribal Population in Kanceepuram District

Abstract: Background: Global epidemic of hypertension is largely uncontrolled, Hypertension is the leading cause of death among non-communicable diseases worldwide. Several criteria was used to assess the prevalence of hypertension among tribal population.Aims and objectives: This study aim to assess the prevalence of hypertension among tribal population Materials and methods: Cross sectional study design, multi stage cluster sampling technique, was used for (Anjur, Kollamedu, Nallambakam, Karanaipuducherrry tribes) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Their evaluation results showed that SMO classifier has given them a higher accuracy of 98.96%, Bagging showed an accuracy of 63.44% and Random Forest showed a lower accuracy of 41.82% which was contrary to the above studies. In the work [6], they have built a computer aided illness diagnosis which will properly detect anemia in a person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their evaluation results showed that SMO classifier has given them a higher accuracy of 98.96%, Bagging showed an accuracy of 63.44% and Random Forest showed a lower accuracy of 41.82% which was contrary to the above studies. In the work [6], they have built a computer aided illness diagnosis which will properly detect anemia in a person.…”
Section: Literature Reviewmentioning
confidence: 99%